Religious Celebrity: The Metamorphosis of Islamic Preachers in Indonesia - Iim Halimatusa’diyah (JURNAL INDO-ISLAMIKA, 2012)
The article critically discusses the transformation of popular Islamic preachers in Indonesia into religious celebrity. One of the explanations is that the phenomenon of this transformation is a direct result of the increasing using of media technology as a new tool in the dissemination of Islamic discourse. Through the support of mass media technology, these contemporary Islamic preachers are easily obtained a wide audience and simultaneously obtained a public recognition. This article, at least, found two important points related to the exploitation of the media. First, people are able to exploit the media as a tool to disseminate religious discourse.  Second, the media can also exploit religion by making it as commodities to gain a greater advantage.